تنفيذ تعليم تحسين الخط العربي لطلاب قسم تعليم اللغة العربية - Dwi Khoirotun Nisa’ (Journal of Calligraphy, 2022)
This reaserch aims to describe the implementation of learning Tahsin al-Khat al-'Araby to students of the Arabic Language Education Program, Faculty of Tarbiyah and Teacher Training, KH Achmad Siddiq State Islamic University Jember. The results showed that the implementation of learning Tahsin al-Khat al-'Araby took place using the demonstration, lecture, and assignment. The goal is that students gain to write Arabic well, correctly, and beautifully, and are able to produce calligraphy works. The guidebooks used in the study are Kurrasah at-Thariqah al-I'tiyadiyyah fi Tahsin al-Kitabah by Sheikh Belaid Hamidy and Qawa'id al-Khath al-'Araby by Sheikh Hasyim Muhammad al-Baghdadi. There are two types of evaluation techniques, summative and formative. Summative evaluation is carried out at the end of each meeting. While formative evaluation is carried out at the end of the semester by making calligraphy works.